An assessment of in vivo failures of alumina ceramic total hip joint replacements - Morrell, Roger; Danzer, Robert; Milošev, Ingrid; Trebše, Rihard (Journal of the European Ceramic Society, 2012)
Several cases of alumina ceramic hip replacement failures are reviewed fractographically. Three main findings are illustrated. Firstly, there is evidence that surgeons can damage the femoral head bore surface during surgery. Secondly, three of the failures described are of extended neck designs which are weaker than those of normal or short length in axial laboratory testing. Under physiological loading, such geometry can lead to levering forces, inappropriate localized contact with the metallic stem and stress concentrations. Delayed failure can ensue, with a fracture pattern quite different from that seen in conventional uniaxial testing. Thirdly, while some failures show head bore surfaces which are clean apart from metallic witness marking, others show brown stains and white deposits suggesting poor conformal contact. We suspect either stems become damaged during surgery before mounting the head or entrapment of debris, pointing to handling care and cleanliness varying between hospitals.